2017
DOI: 10.1186/s12889-017-4037-x
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of the neglected tropical diseases control program in Cameroon: the case of the national program against onchocerciasis

Abstract: BackgroundOnchocerciasis is a severe parasitic infestation which causes disabling skin and subcutaneous tissue changes. Current global estimates suggest that it accounts for 1135.7 disability adjusted life years (DALYs) per 100,000 population. The disease is endemic in many African countries including Cameroon, probably suggesting that the current health policies are inadequate to achieve eradication of the disease. We aimed to appraise the current Onchocerciasis control program in Cameroon in the context of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…Individuals who were residing at less than 2Km distance from the river were nearly nine times more probable to develop the disease as compared to those who resided at greater than or equal to 2 Km distance from the river. This finding was in line with studies done in Cameroon [10]. This could be because those who resided at less than 2Km from the river may be more exposed to black fly bite as compared to their counterparts since black flies breed in the fresh water.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Individuals who were residing at less than 2Km distance from the river were nearly nine times more probable to develop the disease as compared to those who resided at greater than or equal to 2 Km distance from the river. This finding was in line with studies done in Cameroon [10]. This could be because those who resided at less than 2Km from the river may be more exposed to black fly bite as compared to their counterparts since black flies breed in the fresh water.…”
Section: Discussionsupporting
confidence: 90%
“…The study revealed that the overall prevalence of onchocerciasis infection in Semen Bench district after fifteen years of CDTI was 6.32%. The finding was consistent with the findings of studies conducted in southwest Ethiopia, Cameroon, Senegal, and Equatorial Guinea [10,[12][13][14][15][16]. The study was not consistent with the studies done at Jimma zone and West Welega zone which showed the prevalence of 22.5% and 74.8%, respectively [9,17].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…For example, by 2015, after 15 years of CDTI, onchocerciasis was reported to remain mesoendemic in the Centre and Littoral Regions of Cameroon [ 47 ]. In the North and North-West of the country, the prevalence of onchocerciasis had dramatically decreased after 17 years of CDTI but elimination has certainly not yet been reached [ 48 ]. In the DRC not even the target coverage for onchocerciasis morbidity control (of 65%) had been reached by 2012 [ 49 ], let alone the target coverage for elimination (80%).…”
Section: Introductionmentioning
confidence: 99%